Advances in the Diagnosis and Treatment of Acanthamoeba Keratitis. (6th December 2012) - Clarke, Benjamin; Sinha, Arti; Parmar, Dipak N.; Sykakis, Evripidis
Abstract : This paper aims to review the recent literature describing Acanthamoeba keratitis and outline current thoughts on pathogenesis, diagnosis, and treatment as well as currently emerging diagnostic and treatment modalities.